Penerapan Hermeneutika untuk Memaknai Cerita Alkitab dalam Proses Pembelajaran Anak Usia Dini Kristen (Pusat Riset dan Inovasi Nasional, 2026)
The process of Christian Religious Education for early childhood must be aligned with children’s cognitive, emotional, social, and spiritual development. One of the main challenges in this learning process is interpreting biblical stories accurately while maintaining simplicity and relevance for young learners. This study aims to examine the role of hermeneutics in understanding and interpreting biblical narratives used in Christian Religious Education for early childhood. The research employs a qualitative approach through a literature review of hermeneutical studies, biblical texts, and scholarly works on early childhood Christian education. The findings indicate that narrative hermeneutics enables educators to interpret biblical texts contextually while translating theological messages into pedagogically appropriate stories for children. Through a hermeneutical approach, learning becomes more meaningful, reflective, and transformative, fostering deeper spiritual understanding in early learners. Furthermore, hermeneutics helps educators bridge the gap between the theological content of the Bible and the everyday experiences of Christian children. In conclusion, hermeneutics functions as a strategic tool in delivering biblical messages in ways that are developmentally appropriate, spiritually enriching, and relevant to the lives of early childhood learners within Christian education contexts.